Comparative Efficacy and Safety of Nonsurgical Treatment Options for Enthesopathy of the Extensor Carpi Radialis Brevis: A Systematic Review and Meta-analysis of Randomized Placebo-Controlled Trials. Issue 12 (October 2019) - Lian, Jayson; Mohamadi, Amin; Chan, Jimmy J.; Hanna, Phillip; Hemmati, David; Lechtig, Aron; Nazarian, Ara
Background: Numerous treatment options have been proposed for enthesopathy of the extensor carpi radialis brevis (eECRB). Purpose: To (1) compare the efficacy and safety of nonsurgical treatment options for eECRB described in randomized placebo-controlled trials at short-term, midterm, and long-term follow-up and (2) evaluate outcomes in patients receiving placebo. Study Design: Systematic review and meta-analysis. Methods: Following PRISMA guidelines, 4 electronic databases were searched for randomized placebo-controlled trials for eECRB. Studies reporting visual analog scale (VAS) for pain scores and/or grip strength were included. Random- or fixed-effects meta-analysis was employed to compare treatments with at least 2 eligible studies using the standardized mean difference and odds ratio. The study protocol was registered at PROSPERO (ID: CRD42018075009). Results: Thirty-six randomized placebo-controlled trials, evaluating 11 different treatment modalities, with a total of 2746 patients were included. At short-term follow-up, only local corticosteroid injection improved pain; however, it was associated with pain worse than placebo at long-term follow-up. At midterm follow-up, laser therapy and local botulinum toxin injection improved pain. At long-term follow-up, extracorporeal shock wave therapy provided pain relief. With regard to grip strength, only laser therapy showed better outcomes in comparison with placebo. While there was no difference among various treatments in the odds ratio of an adverse event, they all increased adverse events compared with placebo. In placebo-receiving patients, a sharp increase in the percentage of patients reporting mild pain or less was observed from 2% at short-term follow-up to 92% at midterm follow-up. Conclusion: Most patients experienced pain resolution after receiving placebo within 4 weeks of follow-up. At best, all treatments provided only small pain relief while increasing the odds of adverse events. Therefore, if clinicians are inclined to provide a treatment for particular patients, they may consider a pain relief regimen for the first 4 weeks of symptom duration. Patient-specific factors should be considered when deciding on treatment or watchful waiting.